PENGEMBANGAN BUKU BACA TULIS AKSARA LONTARA’ BERBASIS BUDAYA BUGIS UNTUK SEKOLAH DASAR - Kilawati, Andi; Zulham, M; Sunardin (Jurnal Pendidikan Dasar, 2023)
Abstract: Research on the development of Lontara script reading and writing books aims to improve the ability to read and write Lontara script in elementary school students in phase C (class V). This type of research is R&D and uses the ADDIE model (analysis, design, development, implementation and evaluation). This research trial was carried out according to the initial observation location, namely at SDN 106, Barru Regency. The subjects of this research were 17 class V students (phase C). The instruments of this research are tests, questionnaires, interviews and observations. Data was analyzed qualitatively and quantitatively. The cultural expert validation results showed 92% in the very feasible category, the linguist validation results showed 94% in the very feasible category, and the material content validation results showed 90% in the very feasible category. Initial trial results showed that the ability to read and write the Lontara script reached 87% of the category. very good, and in the results of the final trial (large group trial) the students' ability to read and write the Lontara script reached 89.3% in the very good category. This achievement shows that the Lontara script reading and writing textbook is suitable for use as teaching material in improving the Lontara’ script reading and writing skills of class V elementary school students (phase C). Keyword : Reading and Writing, Lontara Script, Bugis Culture